Distributed coordination for a class of non‐linear multi‐agent systems with regulation constraints. Issue 1 (1st January 2018) - Tang, Yutao; Yi, Peng
Abstract : In this study, a multi‐agent coordination problem with steady‐state regulation constraints is investigated for a class of non‐linear systems. Unlike the existing leader‐following coordination formulations, a reference signal is not given by a dynamic autonomous leader but determined as the optimal solution of a distributed optimisation problem. Furthermore, the authors consider a global constraint having noisy data observations for the optimisation problem, which implies that the reference signal is not trivially available with the existing optimisation algorithms. To handle these challenges, the authors present a passivity‐based analysis and design approach by using only local objective function, local data observation and exchanged information from their neighbours. The proposed distributed algorithms are shown to achieve the optimal steady‐state regulation by rejecting the unknown observation disturbances for passive non‐linear agents, which are persuasive in various practical problems. Applications and simulation examples are then given to verify the effectiveness of the proposed design.